The book of Leviticus : composition and reception - Rendtorff, Rolf, 1925-2014; Kugler, Robert A.; Bartel, Sarah Smith (Supplements to Vetus Testamentum ;, 2003)
An examination of the formation, final form, themes and interpretation of the Book of Leviticus. The contributors include Baruch Levine, Jacob Milgrom, Graeme Auld, Alfred Marx, Mary Douglas, Rene Peter-Contesse, Lester Grabbe, Calum Carmichael, Martin McNamara, Robert Kugler and Bruce Chilton.